Design and evaluation of an air-insulated catheter for intra-arterial selective cooling infusion from numerical simulation and in vitro experiment. (January 2022) - Jiang, Miaowen; Li, Ming; Gao, Yuan; Yin, Zhichen; Ding, Yuchuan; Zheng, Yufeng; Zheng, Shiqiang; Wu, Chuanjie; Li, Ang; Fang, Jiancheng; Ji, Xunming
Highlights: Intra-arterial selective cooling infusion (IA-SCI) is a promising neuroprotection technique for ischemic stroke treatment, but the low thermal insulation of cooling catheter inhibits its cooling efficiency. An air-insulated catheter (by sealing air into closed tube chambers) was developed for IA-SCI to achieve the high cooling rate with relatively low amount of cold perfusate. The delivery temperature (14.18°C) of the 4°C perfusate (20 ml/min) through the AI catheter was much lower than that (∼30°C) of its commercially alternatives. Abstract: Intra-arterial selective cooling infusion (IA-SCI) is a promising method for neuroprotection of patients with acute ischemic stroke. One shortcoming of IA-SCI is the elevated delivery temperature caused by the cold perfusate warming along the catheter pathway. Therefore, increasing the thermal resistance of the catheter is of significant importance. In this manuscript, an air-insulated catheter was designed and manufactured through extrusion molding technique. The computational fluid dynamics (CFD)-based thermo-/hemo-dynamics models were exploited to evaluate the thermal conductivity of the catheter. Compared with commercially available endovascular catheters, its thermal insulation property was analyzed through an in vitro experiment. The temperature of the 4°C perfusate (20 ml/min) increased to 14.2°C ± 0.2°C after being transferred to the distal tip of the air-insulated catheter, which was significantly lower than that (30°C) of commercially available alternatives. Moreover, the simulated blood (56% glycerin and 44% bi-distilled water, 37°C) in the middle cerebral artery of the artificial circulating system was cooled down to 29.7°C ± 0.1°C by this perfusate. The cooling process of the brain tissue was also estimated by a biological heat-transfer mathematical model, which showed a 2°C decrease within the initial 1 min infusion. This study demonstrated that the air-insulated catheter for IA-SCI was promising in vitro in terms of its high cooling efficiency and could be a competitive intervention catheter for therapeutic hypothermia.